Socio-technical factors influencing big data analytics adoption in healthcare - Wolseley, Nik Nurdini; Salahuddin, Lizawati; Mohd Aboobaider, Burhanuddin; Raja Ikram, Raja Rina; Hashim, Ummi Rabaah; Abdul Rahim, Fiza (Institute of Advanced Engineering and Science, 2024)
The purpose of this study is to determine the key socio-technical factors influencing big data analytics adoption in healthcare services. A systematic literature review was conducted using peer-reviewed scholarly publications spanning from 2013 to 2023 to illuminate the influencing factors. Twelve papers focused on the factors influencing big data analytics (BDA) adoption in healthcare services were included for review. The factors were divided into four major groups namely i) person, ii) technology, iii) organization, and iv) environment. Analytical skills define a person, whereas technology is characterized by system quality and information quality. Organization support, organization resources, training, data governance, and evidence-based decision-making are all associated with the organization. Finally, government regulations are allocated to the environment. This review presents evidence of the socio-technical factors that influence big data analytics adoption in healthcare services. The findings from this review recommend future big data analytics adoption in healthcare services to carefully evaluate the factors identified in this study.